Small Business Marketing Strategy for Street Vendors (Case Study on Clothing Traders at Senggol Market Makassar) - Winda Winda; Muhammad Rakib; Marhawati Marhawati; Ilham Thaief; Mustari Mustari (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This research aims to find out how strengths, weaknesses, opportunities, threats and marketing strategies applied by clothing traders in The Senggol Market Makassar.This research is qualitative research type. The data used in this study is primary data and secondary data.Data collection techniques used are observation, interview, and documentation.The data analysis technique used is SWOT analysis. The results showed that clothing merchants in Senggol Market implemented marketing strategies by relying on product quality, making sales directly and through internet social media, as well as maintaining good relationships with consumers. Keywords: Marketing Strategy, Small Business, Swot Analysis